Utilization pattern of antenatal health care services among married women of reproductive age group in the rural area of Surendranagar district, Gujarat, India: a community based cross sectional study - Bhimani, Nishant R.; Vachhani, Pushti V.; Kartha, Girija P. (International Journal of Research in Medical Sciences, 2016)
Background: Maternal mortality continues to be a major public health problem. Inspite of the existence of national programmes for improving maternal and child health in India, maternal mortality and morbidity continue to be high. High quality antenatal care is the most important way to reduce the maternal morbidity and mortality. Utilization of Ante natal care (ANC) services is poor in the rural areas, causing significant impact on the health of the mother and ultimately leads to increased maternal morbidity and mortality. Methods: It was a Community based Cross-sectional study. The study was carried out through oral questionnaire method using pre-designed and pretested performa. All the information was collected, compiled and analysed by applying suitable tests. The data was analysed by Statistical Package for Social Sciences (SPSS) and Microsoft word and Excel have been used to generate graphs, tables etc. Results: A total of 403 women were included in the study. Pregnancy registration was done by 88.77% of the women at either government facility or private doctor. Out of total registered women, majority i.e. 54.25% had registered their pregnancy during 2nd trimester. In response to frequency of antenatal visits, study showed that, 59.18% (216) women had availed three or more than three antenatal visits. It was found that 81.92% (299) had taken complete (2 doses) tetanus immunization. About 47% of women had completed full course of iron and folic acid tablets. It was observed that only 46.03% women had availed complete ANC package. Conclusions: Although Antenatal services in India have been created, strengthened and expanded over the years, their output in terms of utilization particularly in rural area is still limited. The present study has brought out many significant socio cultural barriers like caste, women’s literacy, husband’s literacy, occupation of women, socio-economic class and parity of women affecting the utilization of services.